2020
DOI: 10.53599/jip.v2i1.36
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Stres Mahasiswa S1 Keperawatan Tingkat Satu Dalam Menghadapi Wabah Covid 19 Dan Perkuliahan Daring Di Stikes Karya Husada Kediri

Abstract: The Covid-19 outbreak is a new type of disease and is highly contagious. This new virus was previously unknown before infecting many residents of Wuhan, China. This virus is now spreading to most of the world. To prevent its spread, the government urges people to stay at home and learn online. The aimed of this study was to determine the level of stress of first-degree students in the Nursing Study Program at Stikes Karya Husada in dealing with the Covid-10 outbreak and online lectures due to the outbreak. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
4
0
7
Order By: Relevance
“…The results of the research related to the education level of the Bali Poltrada Taruna students were 245 respondents (100%) with D III education. This research is inversely proportional to the research conducted by Sari (2020) The results showed that the majority of students' education levels were 70 respondents (100%) with undergraduate education. Another similar study was conducted by Widiarta and Gozali (2021) said that the majority of students who experienced psychological disorders during online learning during the COVID-19 pandemic were at the DIII stage, with 30 respondents (100%).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The results of the research related to the education level of the Bali Poltrada Taruna students were 245 respondents (100%) with D III education. This research is inversely proportional to the research conducted by Sari (2020) The results showed that the majority of students' education levels were 70 respondents (100%) with undergraduate education. Another similar study was conducted by Widiarta and Gozali (2021) said that the majority of students who experienced psychological disorders during online learning during the COVID-19 pandemic were at the DIII stage, with 30 respondents (100%).…”
Section: Resultsmentioning
confidence: 72%
“…The results of the research on gender characteristics showed that the majority of students from 245 respondents were male, the majority were 158 respondents (64.5%) and the rest were female, 87 respondents (35.5%). This research is inversely proportional to the research conducted by Sari (2020) said that the majority of students who experienced psychological problems were 60 respondents (85.7%) female and 10 male respondents (14.3%). The results of this study are in line with research conducted by Yudiantoro (2020) which said that the majority of students who experienced psychological problems were male as many as 66 respondents (78.6%).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Wabah COVID-19 menimbulkan banyak perubahan dan tekanan. Ditambah dengan keterbatasan aktivitas dan kebosanan selama stay at home juga menjadi stresor tambahan yang menimbulkan stres bagi mahasiswa selama pandemic COVID-19 (Sari, 2020).…”
Section: Pendahuluanunclassified
“…Pada pelaksanaanya ternyata metode pembelajaran ini memiliki berbagai kendala sehingga menjadi beban tersendiri dan membutuhkan adaptasi serta usaha agar dapat berjalan dengan baik (Sari, 2020)…”
Section: Kajian Pustakaunclassified